2016
DOI: 10.22436/jnsa.009.03.19
|View full text |Cite
|
Sign up to set email alerts
|

Banach fixed point theorem from the viewpoint of digital topology

Abstract: The present paper studies the Banach contraction principle for digital metric spaces such as digital intervals, simple closed k-curves, simple closed 18-surfaces and so forth. Furthermore, we prove that a digital metric space is complete, which can strongly contribute to the study of Banach fixed point theorem for digital metric spaces. Although Ege, et al. [O. Ege, I. Karaca, J. Nonlinear Sci. Appl., 8 (2015), 237-245] studied "Banach fixed point theorem for digital images", the present paper makes many notio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 20 publications
0
33
0
Order By: Relevance
“…Definition 1.1: We say that two distinct points , ∈ ℤ are -(or ( , )) adjacent for digital images if they satisfy the followings [13]: Figure 1. Configuration of the digital -connectivity of ℤ , ∈ {1,2} [12,17] For a natural number , 1 ≤ ≤ , two distinct points Using above fact, we can obtain the -adjacency relations of ℤ as follows [13]:…”
Section: Journal Of Mathematical Sciences and Applicationsmentioning
confidence: 99%
See 4 more Smart Citations
“…Definition 1.1: We say that two distinct points , ∈ ℤ are -(or ( , )) adjacent for digital images if they satisfy the followings [13]: Figure 1. Configuration of the digital -connectivity of ℤ , ∈ {1,2} [12,17] For a natural number , 1 ≤ ≤ , two distinct points Using above fact, we can obtain the -adjacency relations of ℤ as follows [13]:…”
Section: Journal Of Mathematical Sciences and Applicationsmentioning
confidence: 99%
“…Concretely, for ⊂ ℤ , we obtain Since the sequence { } is defined in the digital metric space ( , , ), Han [12] observed that the Euclidean distance between any two distinct points , ∈ is greater than or equal to 1 as follows: Proposition 3.1 [12]: In a digital metric space ( , , ), consider two points , in a sequence { } of such that they are -adjacent . .…”
Section: Journal Of Mathematical Sciences and Applicationsmentioning
confidence: 99%
See 3 more Smart Citations